Meningkatkan Sikap Kerjasama Menggunakan Media Pembelajaran NOPOSAM siswa kelas V SD Kanisius Totogan - Mahardika, Dwiyanita Egaresti; Rusmawan, Rusmawan; Hananingrum, Kensi Jati (Paedagogie, 2023)
This study aims to improve the attitude of cooperation using the learning media "NOPOSAM" for fifth grade students at Kanisius Totogan Elementary School. This type of research uses Classroom Action Research which is carried out in two cycles with 2 stages, namely each cycle consisting of observations and interviews. The analysis technique uses quantitative descriptive so that it can describe data about the attitude of cooperation that was successfully implemented at Kanisius Totogan Elementary School. From the results of the Classroom Action Research (CAR) that had been carried out, it was found that 90% of students had been able to apply a cooperative attitude with their classmates very optimally. So it can be concluded that the application of a collaborative attitude using the learning media "NOPOSAM" for fifth grade students at Kanisius Totogan Elementary School has been successful.